Customer Relationship Management Model; A Business Strategy in a Competitive Business Climate - Ben Etim Udoh; Emmanuel Samuel Udo; Abner Ishaku Prince (International Journal of Supply Chain Management, 2019)
Resourceful and effective customer relationship management (CRM) drives the success rate of modern organisations. The global and competitive business climate in Nigeria after the economic crisis spur the need by companies to develop and fortify their model relationship with shareholders especially customers and competitors to remained competitive and retained their customers. The mutual, beneficial and Long-term resourceful relationship established between organisations and their customers offers a business’s competitive advantage in a highly competitive business climate. Lower business cost, increase shareholders’ values and satisfy customers change in taste and fashion. This study examines CRM implementation, benefits, and performance in Nigeria. Findings based on an appropriate questionnaire show companies applying CRM benefits and witness improve performance. Survey results indicate that CRM is a vital strategy and business competitive advantage against competitors. The study recommends the Balanced Scorecard (BSC) model affiliating CRM implementation and performance to spur organizational success in Nigeria.Keywords: Balanced Scorecard, customer relationship management (CRM), competitive business climate, Nigeria, business crisis